Use of multiple data sources and analytical approaches to derive a marine protected area for a breeding seabird. (November 2015) - Perrow, Martin R.; Harwood, Andrew J.P.; Skeate, Eleanor R.; Praca, Emilie; Eglington, Sarah M.
Abstract: Designating Marine Protected Areas (MPAs) is seen to be fundamental to future seabird conservation. In accordance with European Union legislation, the UK proposes to extend Special Protection Areas (SPAs) into the offshore zone for seabirds. This study provides the basis of a foraging range extension to the main UK SPA colony of breeding little tern ( Sternula albifrons ). We applied several established analytical approaches to identify MPAs to multiple data sources including boat-based surveys and individual tracking, alongside a 'foraging radius' approach derived from published foraging range. We pooled data from multiple seasons to account for any inter-annual variation in foraging range and distribution. Minimum convex polygon (MCP), kernel density contours and a linked distance cluster method were performed on tracking data, whereas Generalised Additive Models and kernel density estimation were applied to boat-based survey data. The shape and size of the MPAs produced from analyses of the different datasets were broadly similar to each other, generating confidence in the outputs and suggesting that an integrated approach may have widespread applicability. In contrast, generic foraging radii did not produce representative areas, suggesting restricted use as a preliminary scoping tool. Tracking reflected habitat use of birds of known provenance and a simple approach using 100% MCP provided a clearly defined boundary to feed into marine spatial planning that incorporated all important foraging habitats, embraced threats from anthropogenic development and could 'future-proof' changes in colony location. Where resources are limited, tracking over multiple seasons may be the most efficacious means of deriving seabird MPAs.